Clinicoradiological evaluation and outcome assessment of single-stage posterior correction of atlantoaxial dislocation - Avinash Kumar; Vivek Kumar Kankane; Aditya Srivastava; Avdhesh Shukla; Mayank Jeswani; Avinash Sharma (Asian Journal of Medical Sciences, 2023)
Background: Atlantoaxial dislocation (AAD) refers to loss of stability between atlas and axis vertebrae, resulting in loss of normal articulation. It may be due to congenital, traumatic, or inflammatory reasons. Various techniques of atlantoaxial fixation have been described and used in patients over the years, but each has its own merits and demerits. Aims and Objectives: The aim of the study was to study clinicoradiological evaluation and outcome assessment of single-stage posterior correction of AAD. Materials and Methods: This is a prospective study done in the Department of Neurosurgery, JA group of hospitals, Gajra Raja Medical College, Gwalior, from July 2021 to July 2022. The study was conducted on 20 randomly selected patients whose presentation and imaging showed indication for surgery. Results: C1 lateral mass C2 pars screw fixation had one Frankel grade improvement in 6 months in 96% patient with a fusion rate of 100% and the patient also has modified Japanese orthopedic association score improvement of 15.25±0.98. Conclusion: This study reviewed single-stage posterior correction of AAD using C1 lateral mass and C2 pedicle screw and rod fixation; it enables the stabilization of atlantoaxial motion and preserves motion at occipito-atlantal level with high fusion rates, good neurological recovery, and minimal complications.